Control system analysis and identification with MATLAB® : block pulse and related orthogonal functions - Deb, Anish, 1951-; Roychoudhury, Srimanti, 1984- (Boca Raton, FL : CRC Press, 2019)
This book covers block pulse and related functions for the analysis and identification of continuous and discrete-time systems. It covers 'functions related to block pulse functions' and pulse-width modulated generalized block pulse functions including their applications including MATLAB based examples.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: MATLAB; Automatic control -- Mathematics; Discrete-time systems -- Mathematical models; Functions, Orthogonal; TECHNOLOGY & ENGINEERING / Engineering (General); MATHEMATICS / Applied; TECHNOLOGY / Electricity